Sulphur and particulate matter affecting on soil and underground plants - Haroon Ejaz; Eshrat Bibi; Waqas Ali; Ikhlaq Ahmad; Aamna Lashari; Hadia Faiz; Wajeeha Nazar (Journal of Agriculture and Applied Biology, 2022)
Environmental problems were faced, and one of them is the accumulation of Sulphur and its compounds in the atmosphere and through the atmosphere, it accumulates in the soil and then the underground plants. In the atmosphere Sulphur it is present in the form of aerosols and acid precipitation. Volatile Sulphur compounds are released by the combustion of fossil fuels and volcanic eruption also produces Sulphur oxides. Deficiency of Sulphur produces paling of plants and denaturing of some enzymes that are then fulfilled by using the fertilizers of Sulphur. Soil also has an adverse effect when particulate matter or Sulphur aggregates in the plants and their physiological and biological development is retarded. Most of the industrial processes contain Sulphur compounds like thiol, thiophene, oxides of Sulphur etc. Structural and chemical mutation occurs when particulate substances induce into the plants and productivity and efficiency of that plant is reduced. The impact of acid rain in places with high quantities of mixed air pollutants has yet to be determined. Acid inputs appear to be affecting several techniques in field soils. These must be measured in terms of plant output. SO2 enters the leaves via stomata and quickly dissolves in Apoplastic water, producing mostly Sulphite (SO3)-2, bisulphite (HSO-3), and H+ ions. SO2 phytotoxicity has been attributed to Sulphite and bisulphite ion interactions with different chemicals. If the quantities are not too high, most leaves can detoxify Sulphite and bisulphite by oxidizing them to less harmful Sulphate ions via a series of processes. SO2 absorbed by foliage may undergo reduction conversion, including absorption into organic Sulphur compounds and release from the leaves as H2S. The oxidizing or reducing route of SO2 in plants is determined by plant species, soil Sulphur content, SO2 amount and persistence, and plant growth conditions.